1988
DOI: 10.1128/iai.56.9.2243-2249.1988
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to reinfection after a primary chlamydial genital infection

Abstract: Female guinea pigs which had been infected genitafly with the agent of guinea pig inclusion conjunctivitis were chaflenged at various times after infection with fresh inocula to determine the duration of immunity resulting from the primary infection. At 30 days after infection, most guinea pigs were resistant to reinfection, as indicated by the inability to isolate chlamydiae from cervical swabs. However, at 77, 155, and 294 days, all animals became reinfected, although the course of the infection was abbrevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…This presumption is in accordance with human epidemiologic studies suggesting that prior genital infection with Chlamydia trachomatis, which is phylogenetically highly related to C. suis, confers some short term protection against re-infection [35,36]. Moreover, in all evaluated animal models of genital chlamydial infection, including the mouse [37], guinea pig [38] and macaque [39], it has been demonstrated that at least partial immunity to re-infection develops. Nevertheless, vaginal inoculation with C. suis resulted in an ascending infection in both groups.…”
Section: Discussionsupporting
confidence: 85%
“…This presumption is in accordance with human epidemiologic studies suggesting that prior genital infection with Chlamydia trachomatis, which is phylogenetically highly related to C. suis, confers some short term protection against re-infection [35,36]. Moreover, in all evaluated animal models of genital chlamydial infection, including the mouse [37], guinea pig [38] and macaque [39], it has been demonstrated that at least partial immunity to re-infection develops. Nevertheless, vaginal inoculation with C. suis resulted in an ascending infection in both groups.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, this is the first description of chlamydial antigens not detected in purified EBs. In the guinea pig system, several authors have identified GPIC antigens which are recognized in the context of infection, but the antigens uniformly used in immunoblots were lysates of purified GPIC EBs (3,22,29). Many approaches have been used to examine the antigenicity of MOMP, LPS, and the 60-kDa proteins (2, 30, 32; reviewed in reference 18), and additional EB antigens have been identified in surveys of the antibody response in infected humans and infected or immunized animals.…”
Section: Discussionmentioning
confidence: 99%
“…Hartley strain female guinea pigs, weighing 450 to 500 g, were obtained from Sasco Laboratories, Omaha, Nebr., and were housed individually in an environmentally controlled room with a 12-h light-dark cycle. Guinea pigs were infected in the genital tract with GPIC which had been grown in HeLa cells (15). Each animal received approximately 1.4 x 107 inclusion-forming units contained in 0.05 ml of sucrosephosphate-glutamate buffer (pH 7.4) (18).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Each animal received approximately 1.4 x 107 inclusion-forming units contained in 0.05 ml of sucrosephosphate-glutamate buffer (pH 7.4) (18). The course of the infection was monitored by determining the percentage of inclusion-bearing cells on a Giemsa-stained smear of a scraping from the vaginal vault (15). Antibody titers in serum and genital secretions were determined by an enzyme-linked immunosorbent assay, using GPIC elementary bodies grown in HeLa cells as the antigen (4).…”
Section: * Corresponding Authormentioning
confidence: 99%